Smart Marketing Investments: A Framework for AI-Based Financial Decision Support - Singh, Mahesh; Rao, Manoj Kumar; Jogi, Surendra S.; Pandey, Manoj B.; Sao, Ajit; Chopde, Mahesh (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The use of artificial intelligence (AI) has become an important part of smart marketing investments in the fast-paced world of business and banking. Using AI’s critical skills to improve accuracy, lower risks, and make the best use of resources is a huge step forward in this framework. As the amount and variety of data grows, standard ways of making decisions often don’t work. We need a new way of thinking that uses AI to get useful insights.AI is very important for helping people make financial decisions because it can predict things better than humans can. AI quickly looks at huge information to find patterns, predicts market trends, and gives businesses an edge when making decisions. Being able to predict the future not only helps with strategic planning, but it also helps lower risks. AI models look at both past data and real-time market signs using machine learning algorithms. This lets businesses plan ahead for volatile market conditions and improve their financial stability. The proposed framework necessity of improving marketing funds in a time when allocating resources wisely is very important. With the help of data-driven AI models,and machine learning method for marketing budgets are carefully directed toward outlets and projects that are most likely to bring back the most money. This detailed method makes things run more smoothly, so businesses can quickly adjust to changing market conditions and get the most out of their marketing campaigns. This paper study about the bigger effects of AI-based financial decision support in the digital age, focusing on how it encourages new ideas, flexibility, and adaptation with morden machine learning methods. As companies try to figure out how to operate in today’s complicated markets, this approach is a complete way to use AI’s changing power to make smart and useful marketing investments.